(untitled) (Eurasian Medical Research Periodical, 2023)
Arterial hypertension (AH) is a powerful and modifiable risk factor for the development of macrovascular and microvascular complications of diabetes mellitus (DM). [1,2,4,5] Patients with hypertension and diabetes belong to the group of high and very high risk of developing cardiovascular complications and chronic kidney disease. [3,6,7,9] The combination of type 2 diabetes and hypertension dramatically increases the risk of developing end-stage microvascular and macrovascular diabetic complications: blindness, end-stage chronic kidney disease, lower limb amputation, myocardial infarction, cerebral stroke, and worsens the prognosis and quality of life of patients.